Performance of Optical Mobile Communications with User Mobility and Multiple Light Sources. (14th September 2021) - Dang, Jian; Gao, Jiajun; Zhang, Zaichen; Wu, Liang; Zhu, Bingcheng; Li, Chunguo; Wang, Jiangzhou
Abstract : Optical mobile communication (OMC) is a recently proposed optical wireless communication concept aiming to provide very high-speed data rate optical wireless links for multiple and, in general, distributed mobile users. Previous work analyzed the rate performance of a two-user OMC system without user mobility. This paper extends the rate analysis to multiple users with mobility. The scenario of employing multiple light sources with possible user grouping is also considered. User mobility and multiple light sources lead to new challenges on the system design which are addressed for broadcast downlink communication in this work. Simulations show that user mobility decreases the rate, and the way of how to utilize multiple light sources has great impact on the performance. In particular, simultaneous power division usage of multiple light sources through user grouping and power allocation brings almost no gain as compared with the case of single light source. On the other hand, time division usage of multiple light sources is capable of compensating for the hardware deficiency and thus increasing the rate greatly. It is found that OMC is not only superior to the conventional scheme with nonadjustable channel gains but also outperforms free space optical scheme at high signal-to-noise ratio region.